SUBSTRATE SPECIFICITY OF A GLUCOSE PERMEASE OF ESCHERICHIA COLI - Rogers, Dexter (1962)
Rogers, Dexter (Utah State University, Logan) and Shon-hua Yu. Substrate specificity of a glucose permease of Escherichia coli. J. Bacteriol. 84:877–881. 1962.—A study was made of d-galactose uptake by galactose-negative Escherichia coli strain A (Weigle). Uptake probably occurred through a glucose-permease system, because d-glucose and a variety of nonmetabolizable glucose derivatives inhibited the accumulation of galactose and were themselves accumulated. d-Fructose did not inhibit galactose uptake. 6-Deoxy-d-galactose (d-fucose) was taken up by a different permease system. The glucose permease apparently favored pyranoses, and it required the 6-hydroxyl group of the substrate to a greater extent than any of the other hydroxyl groups. Although much of the absorbed glucose-permease substrate was recovered in the free form, a significant amount was recovered as the 6-phosphate ester. Depending on the conditions employed to study uptake, the 6-phosphate ester could amount to as much as 60% of the absorbed galactose.